The promise for democratic deepening: the effects of participatory processes in the interaction between civil society and local governments. Issue 3 (2nd July 2016) - Bherer, Laurence; Fernández-Martínez, José Luis; García Espín, Patricia; Jiménez Sánchez, Manuel
ABSTRACT: Participatory processes (PPs) implemented around the world in the last 20 years have not led to critical social transformations, as was expected when participatory democracy was first projected. However, this kind of democratic innovation has continued to proliferate. In this context, the political effects of PPs must be examined more closely to understand their influence in deepening, or not, democracy. Based on six Spanish cases, the study focuses on four categories of change (towards inclusiveness, transparency, autonomy, and collaboration) in the relationship between civil society and local government authorities. The findings show a limited capacity of transformation because of the instrumentalization tendencies of political promoters, and the resistance of some social actors.